2019
DOI: 10.1080/23340460.2019.1584539
|View full text |Cite
|
Sign up to set email alerts
|

EU's value-based approach in trade policy: (free) trade for all?

Abstract: is a post-doctoral researcher at the Centre for EU Studies. Her doctoral dissertation studied the EU's cooperation policies towards African, Caribbean and Pacific (ACP) countries. During a two-year assignment at the United Nations Development Programme and United Nations Department for Economic and Social Affairs in New York, she continued working on trade and development issues as trade policy analyst. In 2016, she took up a position at the World Trade Organization in Geneva to work on SPS and TBT related iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…However, this does not seem to be in line with what the European Union has negotiated for trade. Our analysis is in line with Drieghe and Potjomkina [ 63 ] observations that irrespective of the values talk in trade policy, the aim of opening new markets has been pursued with great commitment even if it may not be in compliance with values promoted, requiring either a new narrative for trade policy or a change in negotiation priorities.…”
Section: Discussionsupporting
confidence: 80%
“…However, this does not seem to be in line with what the European Union has negotiated for trade. Our analysis is in line with Drieghe and Potjomkina [ 63 ] observations that irrespective of the values talk in trade policy, the aim of opening new markets has been pursued with great commitment even if it may not be in compliance with values promoted, requiring either a new narrative for trade policy or a change in negotiation priorities.…”
Section: Discussionsupporting
confidence: 80%
“…We argue that: 1) the Commission's response was part of a rhetorical counter-strategy, and 2) that the response was grounded in the MG doctrine introduced by Trade Commissioner Pascal Lamy in 1999. Our study contributes to the literature on the evolution of the EU's trade policy pertaining to both values and market access (Drieghe & Potjomkina, 2019). Our research also complements, and partly challenges, the analysis carried out by Young (2019), who, when comparing the EU's 2010 and 2015-2017 trade strategies, ar-gues that the Commission "over-generalized from an extreme case" and pursued a policy "characterized more by continuity than by change" (p. 3).…”
Section: Rhetorical Responses To Politicization and The Managed Globalization Doctrinementioning
confidence: 87%
“…Constructivist EU trade policy studies show how the language and framing used by the EC helps to justify trade agreements and mute potential opposition by moving the discursive beacons of what trade policy is and should be. Following the opposition against TTIP and CETA, for example, authors have identified a discursive re‐emphasis on the role of ‘values’ in EU trade policy (Drieghe and Potjomkina, 2019), and the ‘managed globalization’ discourse of the end of the 1990s (Garcia‐Duran et al ., 2020) which contributed to pre‐empting criticism. Likewise, Brexit and the election of Donald Trump as US President have been utilized as mutually reinforcing signs of a populist and isolationist trend that the EU should resist, reinforcing the need for the EU to become an even more passionate global leader regarding international trade, integrating opposition vocabulary such as ‘fair’, ‘modern’ or ‘progressive’ into their repertoire (De Ville and Siles‐Brügge, 2019).…”
Section: Exits From the Politicized Decision‐trap In Eu Trade Policymentioning
confidence: 99%